2007
DOI: 10.1532/hsf98.20071065
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Fibrinogen Levels as a Predictor of Postoperative Bleeding after Open Heart Surgery

Abstract: The results of this study suggested that low preoperative fibrinogen level appears to be a useful diagnostic marker to assess the activity of the coagulation system, and that its preoperative level may serve as a potential risk factor for postoperative bleeding after coronary artery bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 25 publications
5
58
0
1
Order By: Relevance
“…This was based upon a small set of data in which four out of four patients showed signs of microvascular bleeding at fibrinogen levels of 0.58 g.dl À1 [28]. Recently, studies in gynaecology, neurosurgery and cardiac surgery have shown an increased risk of bleeding in patients with fibrinogen levels between 1.5 and 2 g.dl À1 [29][30][31][32]. Laboratory measurement of fibrinogen, classically by Clauss, is time consuming and prone to errors at the extremes of values [33].…”
Section: Fibrinogenmentioning
confidence: 99%
“…This was based upon a small set of data in which four out of four patients showed signs of microvascular bleeding at fibrinogen levels of 0.58 g.dl À1 [28]. Recently, studies in gynaecology, neurosurgery and cardiac surgery have shown an increased risk of bleeding in patients with fibrinogen levels between 1.5 and 2 g.dl À1 [29][30][31][32]. Laboratory measurement of fibrinogen, classically by Clauss, is time consuming and prone to errors at the extremes of values [33].…”
Section: Fibrinogenmentioning
confidence: 99%
“…Kraujavimas širdies chirurgijoje išlieka dideliu iššūkiu ir dažnai būna vienas pagrindinių veiksnių, lemiančių baigtis. [5] Pooperacinis kraujavimas po širdies operacijų, literatūros duomenimis, yra susijęs su blogesnėmis pooperacinėmis baigtimis [6,7]. Nustatyta daug rizikos veiksnių, sąlygojančių perioperacinį kraujo netekimą: amžius, mažas kūno paviršiaus plotas, kombinuotos operacijos (AVJSO ir vožtuvų chirurgija), šuntų skaičius (≥ 5), priešoperacinis antiagregantų vartojimas, pailgėjusi DKA trukmė (>150 min.…”
Section: Aptarimasunclassified
“…When investigating congenital fibrinogen defects, more complex and time-consuming tests are employed. There is evidence that the low preoperative fibrinogen concentrations correlate with higher peri-operative blood loss in coronary artery bypass surgery (32,33). Pre-operative prophylactic fibrinogen infusion may be beneficial, although larger trials are required to determine safety and efficacy of this practice (34).…”
Section: Fibrinogenmentioning
confidence: 99%